2009
DOI: 10.1111/j.1749-4486.2009.02033.x
|View full text |Cite
|
Sign up to set email alerts
|

‘When will I see you again?’ Using local recurrence data to develop a regimen for routine surveillance in post‐treatment head and neck cancer patients

Abstract: Local data and published evidence support a follow-up duration of 7 years for laryngeal primaries and 3 years for both oropharyngeal and hypopharyngeal primaries. Late stage oropharyngeal cancers may require longer follow up than early cancers. Patients who continue to smoke may need longer follow up. A change in local follow-up protocol to this regimen would save 10 patient slots every week with no detriment to patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 10 publications
(47 reference statements)
2
37
1
2
Order By: Relevance
“…This seems to support their claim that in general, routine follow-up regimes are rarely indicated after the third year. However, four patients were suspected of recurrence of laryngeal cancer at 220 months; therefore, seemingly supporting claims by Lester et al and Spector et al [5,15] that laryngeal primaries should be followed up for 7 years. Marchant et al [16] suggest that follow-up for life should be considered if detrimental habits such as smoking and alcohol use persist.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…This seems to support their claim that in general, routine follow-up regimes are rarely indicated after the third year. However, four patients were suspected of recurrence of laryngeal cancer at 220 months; therefore, seemingly supporting claims by Lester et al and Spector et al [5,15] that laryngeal primaries should be followed up for 7 years. Marchant et al [16] suggest that follow-up for life should be considered if detrimental habits such as smoking and alcohol use persist.…”
Section: Discussionmentioning
confidence: 85%
“…Their input ensures a more holistic patient approach, and many rehabilitative issues traditionally discussed with the surgeon are more efficiently addressed through their own individual systems. The guidelines outlined in Table 1 differ in their advice as there is currently no high-level evidence to support any one given regime, and many variations exist from region to region [5,13]. The authors believe that a streamlining of the current system to a more modern, efficient one that takes into account geographical variations and individual patient requirements is needed.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Most relapses of head-and-neck cancer occur during the first 3 years, with 80% occurring within 2 years of treatment completion and 95% within 3 years 41 , which supports the observed declining intensity trend. In a U.K. study 37 , data collected locally during a 10-year follow-up period were used to study time to first recurrence and to a new primary. The authors found that, of first cancer events, 95% occurred within the first 3 years for oropharyngeal and hypopharyngeal cancers and within 4.7 years for laryngeal cancer.…”
Section: Discussionmentioning
confidence: 99%